Ultrasonographic measurement of the cross‐sectional area of the axillary nerve. Issue 1 (12th April 2019) - Yoon, Joon Shik; Park, Jung Hyun; Levin, Joshua; Roh, Eugene Y.; Park, Hye Jung; Won, Sun Jae
ABSTRACT: Introduction: The objectives of this study were to determine normal reference values for ultrasonographic measurement of the cross‐sectional area (CSA) of the axillary nerve and to standardize the measurement methods. Methods: Sixty healthy volunteers were evaluated. Ultrasonography was performed with the shoulder positioned in 100°–120° abduction and 90° external rotation. The CSA of the axillary nerve was measured bilaterally. Results: The normal CSA of the right axillary nerve was 2.9 ± 1.1 mm 2 . The side‐to‐side discrepancy was 22.8% ± 17.8%. Discussion: These reference values may be helpful for investigating pathologies involving the axillary nerve.